1982
DOI: 10.1346/ccmn.1982.0300108
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Adsorbed Iron in Montmorillonite by Mössbauer Spectroscopy

Abstract: Abstract--The M6ssbauer effect of Fe 5~ was used to probe and characterize iron ions adsorbed on the interlayer surfaces of montmorillonite. Measurements were performed with Fe-and Ca-saturated montmorillonites. At 210~ the intensity of the Fe z+ line was greatly reduced, apparently due to the melting of interlayer water. Neither the structural Fe 2+ in Ca-montmorillonite nor the adsorbed Fe n+ in Fe-montmorillonite were affected by the melting process. From the temperature dependence of the absorption intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 9 publications
7
33
1
Order By: Relevance
“…Similar behavior has been reported for Fe(II)-exchanged montmorillonite (Diamant et al 1982) and montmorillonite intercalated with dimethyltin(IV) complexes (Simopoulos et al 1988). It was also discussed by Breen et al (1992) in their study of the Sn(II)-clay interactions.…”
Section: Resultssupporting
confidence: 75%
“…Similar behavior has been reported for Fe(II)-exchanged montmorillonite (Diamant et al 1982) and montmorillonite intercalated with dimethyltin(IV) complexes (Simopoulos et al 1988). It was also discussed by Breen et al (1992) in their study of the Sn(II)-clay interactions.…”
Section: Resultssupporting
confidence: 75%
“…Our data suggest that the surface Sn polymer is weakly associated with surface water, and that the change in vibrational freedom of Sn near 210 K is associated with the melting of the latter, as noted by Anderson & Tice (1971). We can, however, find no rationale for the absence of a break in the In A vs. T curve for Fe3+-montmorillonite, in which the Fe 3+ ions were also believed to occur as an oxy/hydroxy coating on the surface of the clay (Diamant et al, 1982). Our results for the SnClz/kaolin system, which cannot have a significant contribution from an interlamellar species in intimate contact with water, also exhibit a discontinuity near 210 K. One possible explanation is that the Sn oxy/hydroxy polymers contain a greater amount of, or are in more intimate contact with, water than the corresponding hydroxyferric aggregates and that this water melts at a temperature close to that of water in the clay micropores.…”
Section: A(t) a Exp[-6ert/kod 2]mentioning
confidence: 78%
“…tightness of binding of the M6ssbauer atom within the system, which it might be anticipated would be greater for an interlayer than for a surface-bound species. Secondly, this vibrational freedom of the interlayer cation is greatly enhanced by the melting of associated water molecules at -210 K, and appears as a discontinuity at this temperature in plots of In A vs. temperature, T. This phenomenon has been used to distinguish interlayer from structural Fe in Fe2+'3+-exchanged montmorillonite (Diamant et al, 1982) and has been more fully treated by Simopoulos et al (1988) in their studies on dimethyltin(IV)-exchanged clay. Because the recoil free fraction,f, and the spectral area, A, are linearly related for "thin absorbers":…”
Section: Discussionmentioning
confidence: 99%
“…Upon Ca-saturation, however, both Fe 2+ doublets were removed (Figure 3b) confirming that the Fe 2 § was in the interlayer instead and at least two distinct interlayer sites are present. Diamant et al (1982) reported interlayer Fe 2 § in montmorillonite with values of $ = 1.04(3) and h = 3.12 (3) ram/see, which differ from those of~ = 1.09 (1) and (2) 4 (1) .... Li-CAL 0.208 (7) 0.506 (7) 0.27 (1) 10 (1) .... Na-KOE 0.192 (4) 0.516 (4) 0.27 (1) 21 (1) .... Ca-WOD 0.187 (7) 0.471 (7) 0.31 (1) 18 (1) .... Ut = untreated; Ca = Ca-saturated; Li = Li-saturated; Na = Na-saturated. 2 Fe3+ for SPO and MAN nontronites, Fe 2 § for BIN nontronite.…”
Section: Resultsmentioning
confidence: 99%